Primary Laryngeal Aspergillosis in an Immunocompetent Host - Kaustuv Das Biswas; Ankit Choudhary; Swapan Kumar Ghosh; Subhradev Biswas (Bengal Journal of Otolaryngology and Head Neck Surgery, 2020)
Introduction